PERAN HUKUM INTERNASIONAL DALAM PENYELESAIAN PELANGGARAN INTERNATIONAL HEALTH REGULATIONS - Raihan Muhammad Prihadi (2022)
WHO as an international organization in the health sector is the largest body in the world that countries rely on for recommendations of actions that need to be taken to improve the welfare of the world community, but the question arises what if a country violates interna- tional provisions, namely the International Health Regulations 2005 (IHR 2005). This study discusses several problem formulations, firstly regarding how International Law plays a role in handling the occurrence of a pandemic, and secondly regarding how the form of settle- ment of IHR 2005 violations occurs based on international law. The research method used is normative legal research. The results showed that the procedures for handling pandem- ics by international law can be divided into prevention, treatment, and international cooper- ation, where most of the procedures are found in the IHR 2005 itself, and state actions that violate the 2005 IHR provisions are essentially inconsistent with the WHO constitution, and those who feel aggrieved by the violation can choose several legal channels by means of non-litigation or litigation. The litigation stage was found to have a legal uncertainty, based on cases using the same principle. The need to revisit the IHR 2005 as an international health provision with provisions such as caution is required for the future.